Teacher research training: a challenge for today’s universities - Hernández, Rubinsten; Moreno, Sandra Maritza (Uptc, 2021)
The selection, organization of content, evaluation of programs, learning and competences, and the implementation of strategies to teach and learn in accordance with the complex and changing needs of today’s society, are just some of the demands that are necessary for schools and teachers today. In order to respond to these facets, an analysis of the relationships between schools, society and knowledge, theory and practice, and training and research is necessary. Teachers are needed who can read, interpret, and makes decisions based on their understanding of a particular context in addition to performing research on their reality in order to transform it. This article reflects on and presents some ideas around this thesis in order to recognize the integrating role challenges have in addition to the challenges posed by today’s society on the teacher.